Needle-use declarations at the Olympic Games Rio 2016. Issue 11 (21st November 2017) - Allen, Molly; Stuart, Mark Campbell; Gribble, Hannah; Budgett, Richard; Pipe, Andrew
Abstract : Aim: We report on the results of the 'IOC Needle Policy' applied during the course of the Games of the XXXI Summer Olympiad in Rio de Janeiro, Brazil. The policy was intended to empower physicians to ensure appropriate clinical use of needles within team medical environments, enhance the safety of those responsible for housekeeping services and others in the Olympic environment, and permit documentation of such procedures as an adjunct to the doping control programme. Any needle use required the submission of an 'Injection Declaration Form' to IOC medical officials. Method: All ' Injection Declaration Forms' were reviewed and archived. The declarations provided basic information regarding the nature of the needle use and the product(s) involved, the physician, athlete and respective National Olympic Committee (NOC). The details of the declarations were subsequently categorised. Results: A total of 367 declarations were received from physicians representing 49 NOCs. Needle-use declarations were more common in athletics, gymnastics, football and aquatics. A single product was administered in 60% of the cases, and more than one product was administered in 40%. The majority of declarations indicated the use of local anaesthetics, glucocorticoids, non-steroidal anti-inflammatory drugs and analgesics. Conclusion: The introduction of a 'Needle Policy' in the Olympic Games setting was intended to minimise the use of needles by non-physicians, promote evidence-based practice and to deter needle-based doping practices. Declarations were received from 49 of 209 NOCs suggesting either that needle use is minimal among certain teams or opportunities remain to enhance compliance with such policies at future games.